Students' Perceptions Toward the Mandatory TOEFL Score for Graduation: A Case Study of Non-English Department Students of the University of Mataram - Nida Silmiya; Yuni Budi Lestari; Ni Wayan Mira Susanti; Boniesta Zulandha Melani (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study explores the perceptions of non-English major students, specifically those in the Mathematics Education program at the Faculty of Teacher Training and Education (FKIP), University of Mataram, toward the mandatory TOEFL score policy as a graduation requirement (minimum 400 for non-English majors). Employing a qualitative case study design, data were collected from 30 eighth-semester students using closed-ended questionnaires (Likert scale) and semi-structured interviews, analyzed through thematic analysis. Findings reveal predominantly positive perceptions (81%), with students viewing the policy as a motivator for enhancing English proficiency and global competitiveness, though 19% deemed it irrelevant to their Mathematics-focused curriculum. Difficulties were prominent, particularly in the Listening Comprehension section (77% reported difficulties due to unclear audio, accents, idioms, and implied meanings), followed by Structure & Written Expression (67%, mainly grammar issues) and Reading Comprehension (60%, with the author's opinion, true/false/exception questions, main ideas/topics, vocabulary/synonyms, word references and restatement of ideas). Interviews highlighted mixed views: benefits for academic access but burdens from time constraints, high costs, and limited preparation support. The study concludes that while the policy effectively measures basic English skills, it imposes undue pressure on non-English majors, recommending intensive TOEFL courses, alternative assessments, and curriculum integration of English skills to mitigate difficulties and foster equitable implementation.